2022
DOI: 10.1177/08959048221087209
|View full text |Cite
|
Sign up to set email alerts
|

State ESSA Plans and Comprehensive Support and Improvement (CSI) Status

Abstract: The Every Student Succeeds Act (ESSA) offers states increased flexibility in how they identify, rank, label, and support underperforming schools. Initial reviews of state ESSA plans, however, suggest that identification and labeling policies have remained relatively unchanged. In this study, we analyze all state ESSA plans to systematically determine how states’ identified Comprehensive Support and Improvement (CSI) schools and the criteria they set for those schools to exit CSI status. We describe our finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Despite many positive perceptions about the relationship and supports provided by the SEA, some leaders noted that it was the process of being held accountable to iteratively producing, reflecting, and continually measuring progress toward goals that was most useful in helping them realize turnaround efforts. This process is one that is put in place by the SEA and is similar in other states (Dunn & Ambroso, 2019;Meyers et al, 2023). However, this study illustrates that it may be important for SEA liaisons as "agents" to form trusting relationships with districts so they can engage in this process productively rather than defensively or as an exercise in compliance.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Despite many positive perceptions about the relationship and supports provided by the SEA, some leaders noted that it was the process of being held accountable to iteratively producing, reflecting, and continually measuring progress toward goals that was most useful in helping them realize turnaround efforts. This process is one that is put in place by the SEA and is similar in other states (Dunn & Ambroso, 2019;Meyers et al, 2023). However, this study illustrates that it may be important for SEA liaisons as "agents" to form trusting relationships with districts so they can engage in this process productively rather than defensively or as an exercise in compliance.…”
Section: Discussionsupporting
confidence: 53%
“…Analyzing 23 state ESSA plans, Dunn and Ambroso (2019) find that they emphasize the role of SEAs in providing resources for LEAs to conduct school turnaround work, and about a third emphasized partnerships between SEAs and LEAs to identify root causes of chronic underperformance, develop improvement plans, and monitor student outcomes which are central to Michigan's Partnership model. A recent study analyzed all ESSA plans and found significant institutional isomorphism across states-specifically, state actors created similar criteria to identify Comprehensive Support and Improvement (CSI) schools and to exit CSI status (Meyers et al, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As many schools nationwide continue to require turnaround interventions (Meyers et al, 2022), simply exploring whether or not such policy initiatives work is no longer adequate, not only because such efforts require high levels of funding from federal and state governments, but also because without understanding more about the factors that impact success or failure, schools and districts operate with limited knowledge about how to utilize such funding. We thus argue that not only is more research needed to understand turnaround efficacy, but also a specific type of research is needed, one that is able to focus on the explanatory factors related to turnaround across contexts.…”
Section: School Turnaround Lessons For Policy and Practice: A Systema...mentioning
confidence: 99%
“…al, 2022). School and district improvement plans facilitate change and enhance student learning (Meyers & VanGronigen, 2021). They are also communication tools for the organization, and a way in which the guiding principles and values of an educational organization are shared (Higano et.…”
Section: Integrate and Make Equity Visible In Guiding Frameworkmentioning
confidence: 99%